Tear metabolomics reveals novel potential biomarkers in epithelial herpes simplex keratitis - Jinyu Zhang; Zhenning Wu; Yangqi Zhang; Kaili Wu; Xiaoyi Li; Shiyou Zhou (BMC Ophthalmology)
Abstract Background Herpes simplex keratitis (HSK) is a recurrent inflammatory disease of cornea primarily initiated by type I herpes simplex virus infection of corneal epithelium. However, early diagnosis of HSK remains challenging due to the lack of specific biomarkers. This study aims to identify biomarkers for HSK through tear metabolomics analysis between HSK and healthy individuals. Methods We conducted a cross-sectional study enrolling 33 participants. Tear samples were collected from one eye of 18 HSK patients and 15 healthy volunteers using Schirmer-strips. Tear metabolomic profiling was performed using high-performance liquid chromatography tandem mass spectrometry (LC–MS/MS). Metabolites were quantified and matched against entries in the human metabolome database (HMDB) and small molecule pathway database (SMPDB) to identify metabolites and metabolic pathways, respectively. Metabolic differences between HSK and control group were determined using multivariate statistical analysis. Results A total of 329 metabolites were identified, of which 18 were significantly altered in HSK patients. Notably, 12 metabolites were significantly increased, and 6 were significantly decreased in HSK patients. The changed metabolites were enriched in these pathways: arginine and proline metabolism, phospholipid biosynthesis, alpha linolenic acid and linoleic acid metabolism, retinol metabolism. To assess the potential utility of tear biomarkers, a predictive model was developed combining 4 metabolites (AUC = 0.998 [95%CI: 0.975, 1]): D-proline, linoelaidic acid, plantagonine, and phosphorylcholine. Conclusions Our study establishes that HSK has a distinctive metabolomic profile, with 4 key elements maybe emerging as potential biomarkers for diagnostic purposes. These findings may provide novel insights into early and rapid diagnosis of HSK.